2018
DOI: 10.1051/matecconf/201816202006
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of brick waste as pozzolanic material in concrete mix

Abstract: Recycling of construction and demolition waste and recycling of industrial by-products into building materials has an enormous potential. Brick waste can be treated by reusing for construction. Recently, the utilization of pozzolanic materials in cement and concrete have increased considerably due to their diverse benefits such as lesser use of cement , saving in production costs, improvement in the durability of concrete and so on. Ground bricks was added to concrete mix as partial replacement of cement at (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The specimens with a 15% substitution ratio showed an increase of 7.5%, 4.4%, and 0.0% in all age groups, respectively, compared to the reference specimens. As in other studies, WBP, together with the pozzolanic reaction, effectively fills the pores and causes a dense micro concrete structure, leading to an increase in strength [ 36 ]. Therefore, WBP below 0.15 mm can play the role of micro-filling and reach a denser state, resulting in an increase in the compressive strength of the mortar [ 30 ].…”
Section: Properties Of Wbp As Scm In Mortar and Concretementioning
confidence: 80%
See 1 more Smart Citation
“…The specimens with a 15% substitution ratio showed an increase of 7.5%, 4.4%, and 0.0% in all age groups, respectively, compared to the reference specimens. As in other studies, WBP, together with the pozzolanic reaction, effectively fills the pores and causes a dense micro concrete structure, leading to an increase in strength [ 36 ]. Therefore, WBP below 0.15 mm can play the role of micro-filling and reach a denser state, resulting in an increase in the compressive strength of the mortar [ 30 ].…”
Section: Properties Of Wbp As Scm In Mortar and Concretementioning
confidence: 80%
“…In many studies, WBP was used as an SCM, replacing cement in the production of mortars and concrete [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In mixtures where waste concrete and brick powder are used together, the replacement ratios and particle size of powders are important when evaluating the fluidity and rheology of the mixture [ 41 ].…”
Section: Properties Of Wbp As Scm In Mortar and Concretementioning
confidence: 99%
“…Studies covering pozzolanic materials have established some improvements of properties of concrete containing brick powder [ 42 , 43 ]. Chloride penetration and sulphate attack on concrete properties are observed to be reduced through inclusion of brick powder [ 42 , 44 ]. The reason perhaps lies in pozzolanic reactivity and micro-aggregate properties which are responsible for suppressing water permeability in concrete, optimising internal pore structure of concrete and increasing concrete compactness [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Capillary absorption is caused by the capillary pressure of the fluid's surface. In penetration, the transport of water is governed by factors like pore connectivity and pore size distribution, other than water accessible porosity, indicating that pozzolanic reaction can refine the capillary pores for water [7]. The results of the capillary absorption test showed that the inhibitor can prevent chloride penetration in concrete by suppressing capillary absorption.…”
Section: Capillary Water Absorptionmentioning
confidence: 99%